Fine Needle Aspiration Cytology: A Useful Technique for Diagnosis of Invasive Fungal Rhinosinusitis - Singhal, Niti (Springer US, 2013)
Mycotic infections are on the rise globally. Patients with invasive fungal infection of the paranasal sinuses often present with destructive mass lesions and mimic malignancy clinically and radiologically. To assess the utility of Fine needle aspiration cytology for early diagnosis of invasive fungal rhinosinusitis. Fine needle aspiration cytology was performed from the maxillary/ethmoid sinus in patients with a destructive mass lesion in the maxilla. Differential diagnoses were malignancy and fungal rhinosinusitis. In eight cases fungi were detected on initial examination whereas in a single case that was initially reported as giant cell lesion, hyphae could be identified within giant cells, on review. Smears showed inflammatory cells with variable numbers of eosinophils with neutrophils and histiocytes. Foreign body giant cells were seen in all cases. The fungi conformed to morphology of aspergillus in seven cases (77.78 %); in two cases (22.22 %), typing could not be done. Periodic acid Schiff and Grocott stains highlighted the fungi in all the cases. Fine needle aspiration is a simple technique that can be useful for diagnosis of fungal rhinosinusitis and to exclude malignancy. Search for fungus may be more aggressive in smears with many foreign body giant cells and inflammatory cells and in cases with a high clinical suspicion. Differentiation between aspergillus and mucor can be made with help of special stains. Aspergillus is the commonest agent isolated. Preoperative cytological diagnosis obviates the need for biopsy, saves time and helps to plan proper treatment.